Mobile Application Design For Learning Digital Engineering Based On Figma And Android Studio - Hariyadi Hariyadi; Herris Yamashika; Waradzi Mustaqim; Alfirdaus Alfirdaus; M. Giatman; Risfendra Risfendra (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2023)
The purpose of this research is to create and implement effective learning media to facilitate lecturers and students in conducting learning at the Electrical Engineering Study Program, Faculty of Engineering, University of Muhammadiyah Sumatera Barat, namely designing Teknik Digital App learning applications by designing using use case diagrams, making the system in accordance with the design that has been made and implement the system that has been created and perform testing on the system. In collecting data, researchers used the method of observation, interviews and literature study. Meanwhile, in developing the system, researchers use the type of Research and Development (RD) research referring to the waterfall model. Applications made using Android Studio, Figma and Adobe Illustrator CS3. The application that has been made is tested using the black box testing method. This research produces a Teknik Digital App learning application that helps parties in carrying out the learning process during lectures and also helps students to make it easier to learn basic digital engineering materials anywhere and anytime.